Cognitive performance in children and adolescents with primary hypertension and the role of body mass - Azukaitis, Karolis; Puteikis, Kristijonas; Kinciniene, Odeta; Mikucionyte, Dovile; Mameniskiene, Ruta; Jankauskiene, Augustina (Frontiers in Pediatrics, 2024)
Objective: Primary hypertension has been shown to affect cognitive functions in adults but evidence in the pediatric population remain scarce and equivocal. We aimed to compare cognitive functioning between children diagnosed with primary hypertension and normotensive controls, with a focus on the role of different blood pressure (BP) indices parameters and body mass.We conducted a single-center, prospective, cross-sectional study of children and adolescents (6-17 years old) with primary hypertension and age-and sex-matched normotensive controls. All children participants underwent office BP, ambulatory blood pressure monitoring (ABPM), and central BP measurements using an oscillometric device. Neurocognitive assessment consisted of evaluation of (i) intelligence quotient (IQ), (ii) categorical and phonemic fluency, (iii) verbal memory (verbal-logical story recall), and (iv) non-verbal computerized cognitive assessment.The study included a total of 59 patients with primary hypertension (14±3 years) and 37 normotensive controls (14±3 years). Children Participants in the primary hypertension group had a significantly higher body mass index z-score (BMIz: 2.1±1.4 vs 0.7±0.9, p<0.001), and 85% received antihypertensive therapy. Children Participants with primary hypertension showed worse performance in the domains of reaction speed, attention and processing speed, visual memory, new learning, and phonemic fluency. After adjusting for BMIz, only the differences in the reaction speed tasks remained significant. None of the BP indices parameters was associated with cognitive outcomes after adjustment for age, sex, and BMIz. BMIz associated with tasks of visual memory, new learning, spatial planning, and working memory, independent of age and sex.Children and adolescents diagnosed with primary hypertension exhibit worse performance in the cognitive domains of reaction speed, attention, processing speed, visual memory, and new learning. These differences to healthy controls , that can also be partially attributed to accompanying increase of body mass.